The role of polyamines in protein-dependent hypoxic tolerance of Drosophila. - Vigne, P.; Frelin, C. (BMC physiology, 2008)
Chronic hypoxia is a major component of ischemic diseases such as stroke or myocardial infarction. Drosophila is more tolerant to hypoxia than most mammalian species. It is considered as a useful model organism to identify new mechanisms of hypoxic tolerance. The hypoxic tolerance of flies has previously been reported to be enhanced by low protein diets. This study analyses the mechanisms involved.Feeding adult Drosophila on a yeast diet dramatically reduced their longevities under chronic hypoxic conditions (5% O2). Mean and maximum longevities became close to the values observed for starving flies. The action of dietary yeast was mimicked by a whole casein hydrolysate and by anyone of the 20 natural amino acids that compose proteins. It was mimicked by amino acid intermediates of the urea cycle such as L-citrulline and L-ornithine, and by polyamines (putrescine, spermidine and spermine). alpha-difluoromethylornithine, a specific inhibitor of ornithine decarboxylase, partially protected hypoxic flies from amino acid toxicity but not from polyamine toxicity. N1-guanyl-1,7 diaminoheptane, a specific inhibitor of eIF5A hypusination, partially relieved the toxicities of both amino acids and polyamines.Dietary amino acids reduced the longevity of chronically hypoxic flies fed on a sucrose diet. Pharmacological evidence suggests that the synthesis of polyamines and the hypusination of eIF5A contributed to the life-shortening effect of dietary amino acids.